The effect of thermal modulation on double diffusive convection in the presence of applied magnetic field and internal heat source - Manjula, S.H.; Suresh, P.; Rao, M.G. (Zielona Góra: Uniwersytet Zielonogórski)
The investigation of thermal modulation on double-diffusive stationary convection in the presence of an applied magnetic field and internal heating is carried out. A weakly nonlinear stability analysis has been performed using the finite-amplitude Ginzburg-Landau model.
Keywords: thermal modulation; weak nonlinear analysis; internal heating; Newtonian fluid; double diffusive convection